2019
DOI: 10.1016/j.intfin.2019.101139
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraints, stock liquidity, and stock returns

Abstract: This paper examines stock liquidity in explaining the mixed relations between financial constraints and stock returns and the pricing of stock liquidity across financially constrained and unconstrained firms. We find a negative relation in liquid portfolios and a positive relation in illiquid portfolios. Financially constrained firms have higher liquidity risk and earn a higher illiquidity premium than unconstrained firms. Financial constraints cannot be independently priced in stock returns and can only be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 93 publications
(139 reference statements)
0
7
0
Order By: Relevance
“… Brogaard, Li & Xia (2017) suggested that a decrease in the market value of a firm and stock price illiquidity increases the likelihood of default. Similarly, Mselmi, Hamza, Lahiani & Shahbaz (2019) and Li & Luo (2019) provided evidence on the pricing of financial distress. In this context, we consider three possible shocks to market capitalization.…”
Section: Stress Scenarios and Datamentioning
confidence: 96%
“… Brogaard, Li & Xia (2017) suggested that a decrease in the market value of a firm and stock price illiquidity increases the likelihood of default. Similarly, Mselmi, Hamza, Lahiani & Shahbaz (2019) and Li & Luo (2019) provided evidence on the pricing of financial distress. In this context, we consider three possible shocks to market capitalization.…”
Section: Stress Scenarios and Datamentioning
confidence: 96%
“…Stock liquidity drives investors' sentiments (Asem et al, 2016) and dividend policies (Nguyen, 2020), and it is always associates with minimum equity floatation cost (Belkhir et al, 2020). It controls ex-ante stock excess return (Amihud, 2002;Li & Luo, 2019); therefore, the investors are enthusiastic about investing in those firms whose equity is highly liquid. The positive effects of stock liquidity on shareholder value reinforce effective governance (Cheung et al, 2015).…”
Section: Capital Market and Trade Credit Policiesmentioning
confidence: 99%
“…In corporate finance, a vital concern is the influence of financial constraints on performance and behavior of firms (Li and Luo 2019). Kurt (2018) indicates that financial constraints have great influence on the accounting information quality.…”
Section: Introductionmentioning
confidence: 99%